PROSPEK IMPLEMENTASI SAK ETAP BERBASIS KUALITAS LAPORAN KEUANGAN UMKM - Susanto, Barkah; Yuliani, Nur Laila (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
The purpose of this study is to evidence the factors that influence the perception of the importance of entrepreneurs related to accounting and financial reporting efforts and understanding SME entrepreneurs as well as proving the influence of the quality of financial reports to the growing number of bank credit received by SMEs in the City and County of ex-Kedu residency. Plan activities will include sampling with purposive sampling, data collection, and then tested by regression analysis testing tool. The results of the data analysis can be concluded that the respondent SMEs in this study have the perception that the accounting and financial reporting is important in the growth and development of its business. Latest education has positive influence on the perception of respondents about the importance of entrepreneurs financial reporting, whereas educational background, gender, and longstanding business has no effect on the perception of entrepreneurs about the importance of financial reporting. Quality of the SME financial statements affect the amount of credit it receives. Entrepreneurs variable information, socialization and last education of the SME entrepreneurs affect the understanding of the content SAK ETAP.